Neuropeptide Y modulates the electrical activity of subfornical organ neurons - Lauren Shute; Mark Fry (Current Research in Neurobiology)
The subfornical organ (SFO) is a sensory circumventricular organ, lacking a blood-brain barrier. It is well-recognized as a key center for detection and integration of osmotic, ionic and hormonal signals for maintenance of hydromineral balance and cardiovascular regulation. Recently, the SFO has also been recognized as a center for the detection and integration of circulating satiety signals for regulation of energy balance. Neuropeptide Y (NPY) is a multifunctional neuropeptide, with effects on energy balance, cardiovascular tone and other aspects of homeostasis. Interestingly, despite the overlap of function between SFO and NPY, and observations that SFO expresses several subtypes of Y receptors, NPY regulation of SFO neurons has never been investigated. In this study, we examined the effects of NPY on dissociated rat SFO neurons using patch clamp electrophysiology. We observed that 300 nM NPY caused depolarization of 16 % of SFO neurons tested, and hyperpolarization of 26 %, while the remaining neurons were insensitive to NPY (n = 31). These effects were dose-dependent with an apparent EC50 of 3.9 nM for depolarizing neurons and 3.5 nM for hyperpolarizing neurons. Activation of Y5 receptors alone led to predominately hyperpolarizing effects, while activation of Y1 or Y2 receptors alone led to mixed responses. Voltage-clamp experiments demonstrated that NPY caused increases in voltage-gated K+ current amplitude as well as hyperpolarizing shifts in persistent Na+ current, mediating the hyperpolarizing and depolarizing effects, respectively. These findings indicate that NPY elicits direct electrophysiological effects on SFO neurons, suggesting that NPY acts via the SFO to regulate energy homeostatic function.